Mutation-Derived Neoantigens for Cancer Immunotherapy - Castle, John C.; Uduman, Mohamed; Pabla, Simarjot; Stein, Robert B.; Buell, Jennifer S. (Frontiers in Immunology, 2019)
Mutation-derived neoantigens distinguish tumor from normal cells. T cells can sense HLA-presented mutations, recognize tumor cells as non-self, and destroy them. Immunotherapy antibodies can increase the virulence of the immune system by increasing T-cell cytotoxicity and decreasing regulatory T-cell activity. Neoantigen vaccines act through antigen-presenting cells, such as dendritic cells, to activate patient-endogenous T cells that recognize vaccine-encoded mutations. Infusion of mutation-targeting T cells by adoptive cell therapy (ACT) directly increases the number and frequency of cytotoxic T cells recognizing and killing tumor cells. Publicly-funded consortia have profiled tumor genomes across indications and determined the mutations in each tumor. Here, with an eye toward immunotherapy applications, we review the spectrum of mutations in multiple indications, show variations in indication sub-types, and examine intra- and inter-indication prevalence of re-occurring mutation neoantigens that could be used for warehouse vaccine and ACT.